ASEtrap: A biological method for speeding up the exploration of spliceomes - Thill, Gilbert; Castelli, Vanina; Pallud, Sophie; Salanoubat, Marcel; Wincker, Patrick; de la Grange, Pierre; Auboeuf, Didier; Schächter, Vincent; Weissenbach, Jean (Genome Research, 2006)
Alternative splicing (AS) of pre-messenger RNA is a major mechanism for generating protein diversity from a limited number of genes in higher eukaryotes, and it constitutes a central mode of genetic regulation. Thus, efficient methods are needed to systematically identify new AS events at a genomic scale across different tissues, stages of development, and physiological or pathological conditions in order to better understand gene expression. To fulfill this goal, we have designed the ASEtrap, which is a cloning procedure for producing AS libraries that is based on a single-stranded trap consisting of an ssDNA-binding protein. In this paper, we have applied our approach to the construction of an AS library and a Control library from human placenta. By analyzing 9226 and 9999 sequences of the AS and Control libraries, respectively, we show that internal AS events (events that can be identified by the sole resources provided by either the AS or the Control library) and the discovery rate of new AS events measured at early stages of sequencing were nine to 10 times higher in the former than in the latter. Moreover, by performing a search for new AS events within a group of 162 known drug target genes, we identified six new events in six genes, and we observed that they all were discovered exclusively through the AS library. Thus, it appears that ASEtrap has the potential to greatly facilitate the determination of the total complement of splice variants expressed in human, as well as other organisms.